The resource curse revisited: Governance and natural resources - Matthias Busse; Steffen Gröning (Hamburgisches WeltWirtschaftsInstitut (HWWI), 2011)
The paper analyses the impact of natural resource abundance on selected governance indicators. In contrast to earlier studies that are mainly confined to cross-sectional analysis, we use a panel data set with a large number of countries and an extended period of time. Moreover, we employ an instrumental variable technique to account for endogeneity. The results show that exports of natural resources have, above all, led to an increase in corruption. This result is robust to both different model specifications and an alternative indicator for natural resource abundance. For other governance indicators, such as law and order and bureaucratic quality, we either find no results or results that lack robustness.
Keywords: F10; O13; Q32; 330; Natural Resources; Resource Curse; Corruption; Governance